Estudo de viabilidade técnica da utilização de gesso reciclado em revestimentos internos - Staldoni, Aline (Universidade do Vale do Rio dos Sinos, 2022)
Gypsum is a material that due to its functionalities has been increasingly used in construction sites. As a result, the amount of waste generated from this type of material and the concern with environmentally correct disposal also grows. In order to reduce the amount of waste that is sent to the final destination, this work seeks to develop a technically viable alternative for the recycling of gypsum waste from renovation and demolition works. Gypsum residues of different origin were collected in two works. After collection, the waste went through the steps of removing impurities, manual crushing, drying, grinding and calcination, generating RGA (first work), RGB and RGC (second work) waste. The calcination was carried out at 150ºC, 170ºC and 190ºC for 2hs and 4hs. After these steps, the specimens were molded and the granulometry, setting time, surface hardness, flexural tensile strength (RT) and compressive strength (RC) tests were carried out, where the influence of time, temperature, granulometry and the type of residue studied. After the analyses, the best results were obtained with the RGC residue calcined at 150ºC for two hours. It was possible to perceive, in general, that: The increase in the calcination time tends to improve the properties of resistance to traction and compression and to decrease the surface hardness; The temperatures studied affected the different types of waste in different ways; The granulometric difference between the samples did not cause significant influence in the RT and RC tests and that the RGB residue has better performance than the RGA residue. The results obtained indicate that gypsum can be recycled and reused in civil construction, however, more studies are indicated to fully meet the requirements of the standard.
Keywords: Gesso; Resíduo de gesso; Resíduo de construção e demolição; Reciclagem de gesso; Placas de gesso; Gipsum; Gypsum plaster waste; Construction and demolition waste; Gypsum plaster recycling; Gypsum plasterboards